Workspace Color and Repetitive Assembly Performance: A Quasi-Experimental Study of a Simple Product Task - Muhammad Nur Wahyu Hidayah; Galih Mahardika Munandar; Barkah Waladani; Imam Samsul Ma'arif (JTI: Jurnal Teknik Industri, 2026)
This study examined whether wall color conditions were associated with differences in repetitive assembly performance during a controlled simulated task. A quasi-experimental between-subjects design was applied involving 116 student participants aged 18–22 years. Participants were allocated through stratified randomization based on age and sex into four identical rooms with matte-painted red, white, blue, or green walls, with 29 participants in each condition, consisting of 15 male and 14 female participants. Environmental and procedural factors, including lighting at 550 lux, temperature at 24 °C, ambient noise at 75 dBA, equipment, instructions, task model, and 30-minute session duration, were standardized. All groups were tested concurrently to minimize temporal variation. After an initial practice opportunity, participants completed the same 10-component toy truck assembly task. Performance was assessed using completion time, accuracy, and productivity. Because the data did not fully satisfy parametric assumptions, Kruskal-Wallis tests were used, followed by Holm-adjusted Mann-Whitney comparisons. The results showed significant differences across wall color conditions for completion time, accuracy, and productivity. Green produced the strongest observed performance profile, with a mean completion time of 3.38 minutes, accuracy of 92.24%, and productivity of 6.30 correct assemblies per minute, followed by blue. These findings suggest that wall color may function as a supplementary environmental ergonomics factor in repetitive manual assembly settings. However, the results should be interpreted as evidence for controlled pilot evaluation rather than as a definitive industrial color standard. Keywords: Workspace Color; Environmental Ergonomics; Repetitive Assembly; Productivity; Accuracy